2019
DOI: 10.1016/j.redox.2018.101088
|View full text |Cite
|
Sign up to set email alerts
|

Statin treatment, oxidative stress and inflammation in a Danish population

Abstract: Background While statins may have anti-inflammatory effects, anti-oxidative effects are controversial. We investigated if statin treatment is associated with differences in oxidatively generated nucleotide damage and chronic inflammation, and the relationship between nucleotide damage and chronic inflammation. Methods We included 19,795 participants from the Danish General Suburban Population Study. In 3420 participants, we measured urinary 8-oxodG and 8-oxoGuo by liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…In the Danish General Suburban Population Study, inflammatory markers were analyzed in 2,922 statin users and 16,873 non-users ( Sørensen et al, 2019 ). In this study, the neutrophil-lymphocyte ratio was reduced by 3% among statin users (95% CI 1 to 5%, p = 0.003).…”
Section: Neutrophil—lymphocyte Ratiomentioning
confidence: 99%
“…In the Danish General Suburban Population Study, inflammatory markers were analyzed in 2,922 statin users and 16,873 non-users ( Sørensen et al, 2019 ). In this study, the neutrophil-lymphocyte ratio was reduced by 3% among statin users (95% CI 1 to 5%, p = 0.003).…”
Section: Neutrophil—lymphocyte Ratiomentioning
confidence: 99%
“…It was suggested that the restoration of neuronal nitric oxide synthase expression and the phosphorylation of Akt in Schwann cells were associated with the neuroprotective effects of rosuvastatin [ 33 ]. Several previous studies reported the anti-inflammatory and anti-oxidative effects of statins [ 34 , 35 ]. In the Danish General Suburban Population Study that enrolled 19,795 participants, statin users showed lower levels of markers for oxidative damage and chronic inflammation than non-users [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin has an antioxidant effect by reducing the production of free radicals, such as peroxide, and prevents a decrease in the activity of antioxidant enzymes (catalase and peroxide dismutase) [48]. Statins, due to their antioxidant activity by inhibition of NAD(P)H oxidase and active exchange of free radicals [49,50,51], reduce chronic inflammation [52], and thus reduce oxidative stress [53]. Ang II inhibitor may selectively reduce Ang II, endothelin, and oxidative stress levels, which may potentially play a role in the lowering of blood pressure [54].…”
Section: Discussionmentioning
confidence: 99%